Zmiany jakości wód w rzekach Łutownia i Perebel w Puszczy Białowieskiej - Janek, Magdalena (Leśne Prace Badawcze, 2016)
The aim of the study was to determine changes in water quality, including chemistry of outflow from two rivers: Łutownia and Perebel located in the Białowieża Primeval Forest. Water chemistry was investigated once in every three months in the years 2011–2014. Catchments differed in forest cover and habitat types. The results of the analysis of river waters were compared with the limit values for each class of water quality as settled by the legal standards. It was found that the quality of the water in rivers declined due to high concentrations of carbon and nitrogen organic forms. In general, there was observed a decrease of the concentration of organic nitrogen and an increase of the concentration of mineral nitrogen, especially in the Perebel catchment area.